Direct elections and trust in state and political institutions: Evidence from Indonesia's election reform - Ridho Al Izzati; Teguh Dartanto; Daniel Suryadarma; Asep Suryahadi (Asian Development Bank Institute (ADBI), 2024)
People's trust in state and political institutions is a key foundation of a well-functioning economy. We estimate the impact of direct elections on people's trust in state and political institutions, using a major political reform in Indonesia as the source of exogenous variation. Prior to 2005, regents, mayors, and governors were elected by the local legislative assembly. Since 2005, however, they have had to compete in an open election where voters directly choose their preferred leader. The historically and institutionally driven staggered implementation of these local direct elections allow us to identify the causal impact of the reform. We find that district direct elections increase trust in all state and political institutions, except for the police. However, our finding does not hold in districts that experienced moderate or high hostility during the elections, implying that trust is strongly influenced by the political situation. We also empirically show that the increase in trust took place simultaneously with improvements in economic outcomes.
Keywords: D72; H10; K16; P51; Z13; 330; democracy; direct election; trust; institution; Indonesia